COMMUNITY SERVICE EDUCATION ON THE USE OF TAMORILLO FRUIT IN AN EFFORT TO INCREASE HEMOGLOBIN LEVELS IN PREGNANT WOMEN IN THE FIRST TRIMESTER WITH HIGH RISK AT THE HANA KASIH CLINIC - Willhelmina Wahara; Barirah; Santalia Laoli (Jurnal Masyarakat Indonesia (Jumas), 2025)
Pregnancy, especially in the first trimester, is a golden period as well as a very vulnerable phase due to the process of organogenesis or the formation of fetal vital organs. In this phase, the nutritional needs of pregnant women increase dramatically to support the growth of new cells and blood volume. However, the main challenge that is often faced is the occurrence of iron deficiency anemia, which if it occurs in pregnant women with high risk categories, can trigger serious complications such as abortion, fetal growth retardation in the womb (IUGR), to the risk of life-threatening post-saline hemorrhage. This community service activity aims to provide structured education on the use of Tamarillo fruit for high-risk first trimester pregnant women at Hana Kasih Clinic. The program will be implemented on July 23, 2025 through interactive counseling methods, educational dialogues, and counseling sessions to empower pregnant women to be able to carry out independent nutrition interventions in a sustainable manner. By integrating local fruit consumption into the daily diet, it is hoped that the hemoglobin levels of pregnant women can be optimally maintained, so that the quality of the mother's health and the fetal growth and development process can be guaranteed in order to reduce maternal and infant mortality in the region.